A five year review of paediatric burns and social deprivation: Is there a link?. Issue 6 (September 2017) - Richards, Helen; Kokocinska, Maria; Lewis, Darren
Highlights: Investigation of possible link between burn incidence and social deprivation. Slight association between burn incidence and social deprivation. Increased burn incidence in certain ethnic groups. No difference in first aid provision across different groups. Abstract: Aim: To establish if there is a correlation between burn incidence and social deprivation in order to formulate a more effective burns prevention strategy. Methods: A quantitative retrospective review of International Burn Injury Database (IBID) was carried out over a period from 2006 to 2011 to obtain data for children referred to our burns centre in West Midlands. Social deprivation scores for geographical areas were obtained from Office of National Statistics (ONS). Statistical analysis was carried out using Graphpad Prism. Results: 1688 children were reviewed at our burns centre. Statistical analysis using Pearson correlation coefficient showed a slight association between social deprivation and increasing burn incidence r 2 = 0.1268, 95% confidence interval 0.018–0.219, p value < 0.0001. There was a slight male preponderance (58%). The most common mechanism of injury was scalding (61%). The most commonly affected age group were 1–2 year olds (38%). There were statistically significant differences in the ethnicity of children with significantly more children from Asian and African backgrounds being referred compared to Caucasian children. We found that appropriate first aid was administered in 67% of cases overall. We did not find a statistically significant link between first aid provision and social deprivation score. Discussion: There was only a slight positive correlation between social deprivation and burn incidence. However, there did not seem to be any change in mechanism of burn in the most deprived groups compared to overall pattern, nor was there a significant difference in appropriate first aid provision. Conclusion: It would seem that dissemination of burn prevention strategies and first aid advice need to be improved across all geographical areas as this was uniformly lacking and the increased burn incidence in more socially deprived groups, although present, was not statistically significant.